Sistem Informasi Pendataan Tabungan Nasabah Pada Bank BTN Bandung - Agung Wahana; Selly Selly (STMIK Mardira Indonesia, Bandung, 2015)
By the rapid growth in information technology sector and the need for rapid and accurate information which can support the decision making, the computerized data processing is one alternative in providing a reliable information. This research was conducted to provide a solution for business on the problem of data processing of accounts receivable such as the receivable which passed the due, data copying and error on the receivable data calculation that led to inaccurate report. Of this research is designed a accounts receivable data processing application that have aging analysis of receivable which can classify the data accounts that passed the due, automatic numbering to avoid data duplication and accounting calculations that can provide convenience for the user to present an accurate report and useful for management decision making. There is method even research that is utilized in this research, the method is waterfall system development method consisting of study feasibility, system design, implement and system evaluation. By using programming languages Visual Basic 6, the final result obtained from this study is an Information Systems of Data Processing Accounts Receivable. Keywords: information system; account receivable; waterfall; visual basic